1997
DOI: 10.1097/00007890-199705150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Human Natural Killer Lymphocytes Directly Recognize Evolutionarily Conserved Oligosaccharide Ligands Expressed by Xenogeneic Tissues1

Abstract: Collectively, our findings suggest that humoral and cellular components of the natural immune response against heterologous species independently evolved recognition patterns directed against overlapping carbohydrate determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 32 publications
3
63
2
Order By: Relevance
“…Finally, the blocking experiments suggest that NK cells were only marginally involved in the proliferation of human PBMC in response to PIC. Since adult PIC do not bear the Gala(1,3)Gal epitope [16], our observation is contrary to reports of recognition of pig endothelial cells by human NK cells through the Gala(1,3)Gal epitope [17], even though the islet preparations could be contaminated by Gala(1,3)Gal-positive endothelial cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, the blocking experiments suggest that NK cells were only marginally involved in the proliferation of human PBMC in response to PIC. Since adult PIC do not bear the Gala(1,3)Gal epitope [16], our observation is contrary to reports of recognition of pig endothelial cells by human NK cells through the Gala(1,3)Gal epitope [17], even though the islet preparations could be contaminated by Gala(1,3)Gal-positive endothelial cells.…”
Section: Discussioncontrasting
confidence: 99%
“…High frequencies (70-90%) of § -Gal-positive EC were obtained, which enabled us to evaluate the effect of this epitope on human NK cell adhesion and cytotoxicity assays in which primary EC with otherwise identical genetic background were used as controls. In contrast to some investigators [6][7][8]23] and in agreement with others [9], we could not detect any significant effect of § -Gal expression on NK cell adhesion, cytotoxicity or IFN-+ production (Fig. 5, 6).…”
Section: Discussionsupporting
confidence: 84%
“…Such an interaction could contribute to later appearing organ xenograft rejection processes, for example acute vascular rejection [5]. Inverardi et al [6] were the first to suggest that there could be direct cellular recognition of, among other epitopes, the § -Gal determinant; human NK cells were shown to bind COS-7 cells expressing the porcine § 1,3 galactosyltransferase ( § 1,3GalT) and § -Gal but did not bind to non-transfected cells [6]. Artrip et al [7] and Miyagawa et al [8] found that reduced expression of § -Gal on pig EC led to reduced sensitivity to direct NK cell-mediated cytolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that NK cells play a critical role in swine to human xenotransplantation (46,47). Thus, an investigation of the effect of enzymatic remodeling of a glycoantigen, especially ␣-Gal, to NK-mediated direct cytotoxicity was carried out using the PEC from the transgenic pig.…”
Section: Fig 5-continuedmentioning
confidence: 99%